2010
DOI: 10.1074/jbc.m110.172767
|View full text |Cite|
|
Sign up to set email alerts
|

Gossypol Induces Death Receptor-5 through Activation of the ROS-ERK-CHOP Pathway and Sensitizes Colon Cancer Cells to TRAIL

Abstract: Development of resistance to TRAIL, an apoptosis-inducing cytokine, is one of the major problems in its development for cancer treatment. Thus, pharmacological agents that are safe and can sensitize the tumor cells to TRAIL are urgently needed. We investigated whether gossypol, a BH3 mimetic that is currently in the clinic, can potentiate TRAIL-induced apoptosis. Intracellular esterase activity, sub-G 1 cell cycle arrest, and caspase-8, -9, and -3 activity assays revealed that gossypol potentiated TRAIL-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
72
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 50 publications
8
72
0
Order By: Relevance
“…MAPKs are important downstream mediators of ROSinduced signalling [26]. ERK, JNK, and p38 MAPK have been found to be activated in TRAILmediated apoptosis [15,30] and are involved in TRAIL receptor induction [15,26]. In our study, the significant increases in the activation of JNK and ERK, along with a considerable increase in p38 MAPK activation on exposure to tangeretin, could have been either due to direct stimulation of tangeretin and/or in part indirectly due to ROS.…”
Section: Rosmentioning
confidence: 47%
See 3 more Smart Citations
“…MAPKs are important downstream mediators of ROSinduced signalling [26]. ERK, JNK, and p38 MAPK have been found to be activated in TRAILmediated apoptosis [15,30] and are involved in TRAIL receptor induction [15,26]. In our study, the significant increases in the activation of JNK and ERK, along with a considerable increase in p38 MAPK activation on exposure to tangeretin, could have been either due to direct stimulation of tangeretin and/or in part indirectly due to ROS.…”
Section: Rosmentioning
confidence: 47%
“…The observed ROS levels could have also induced CHOP expression, because CHOP is a major stress-regulated protein [25]. Several studies have reported that chemotherapeutic agents enhance DR5 expression and TRAILmediated apoptosis via ROS-dependent pathways [15,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous reports, the down-regulation of c-FLIP by the peroxisome proliferator-activated receptor (PPAR)-γ agonist rosiglitazone has been shown to sensitize cells to TRAIL [34]. Gossypol, a polyphenol derived from cottonseed oil, down-regulated the expression of Bcl-2, Bcl-xL and survivin, all of which have been linked to tumor cells to TRAIL [35]. Acrolein also down-regulated the expression of Bcl-2 (Fig.…”
Section: Discussionmentioning
confidence: 82%